Introduction to a special section: Balancing scientific and societal impact—A challenging agenda for academic research. (9th May 2018) - Ramos-Vielba, Irene; D'Este, Pablo; Woolley, Richard; Amara, Nabil
Abstract: There is an increasing social expectation regarding the joint realisation of scientific and societal impact from publicly funded research. Achieving this goal involves facing important challenges, which affect individual researchers, research performing organisations, and the science governance system as a whole. This special section includes conceptual, methodological, and empirical papers that aim to contribute to the building of an improved appreciation of the factors and dynamics shaping the intertwined quest for scientific quality and societal impact.